Targeted Antenatal Screening for Predicting Postpartum Thyroiditis and Its Evolution Into Permanent Hypothyroidism - Benvenga, Salvatore (Frontiers in Endocrinology, 2020)
Postpartum thyroiditis (PPT) has a prevalence of 1 to 22%, with an approximate 50% rate of evolution into permanent hypothyroidism (PH). PPT risk is assessed by measuring serum thyroid antibodies during gestation, as 1/3 to 1/2 of Ab+ve pregnant women will develop PPT. Family and personal history positive for autoimmune nonthyroid diseases (AINTDT), and consumption of swordfish increases while consumption of small oily fish decreases the risk of PPT. Monitoring thyroid function in a very high-risk subgroup avoids the costs of the Ab-based universal screening. We aimed at identifying such subgroup in 412 women followed from week 7-11 of gestation to month 12 postpartum. At study entry, we measured serum TPOAb,TgAb, TSH,FT4,FT3, and evaluated seafood consumption, familial history for thyroid diseases and AINTD, and personal history for AINTD. We measured TSH,FT4,FT3 at 1.5,3,6 and 12 months postpartum. PPT occurred in 63 women (15.3%), and PH in 34/63 (54%). Based on positivity/negativity for the three histories, women were classified into 8 categories, with PPT rates of 3.8% to 100%. Seafood consumption allowed further separation of subgroups having different PPT risks. We considered 11 possible strategies, termed [a] through [k]. Strategy [a] consisted in omitting gestational screening, while performing universal postpartum monitoring with TSH and one thyroid hormone; strategy [k] consisted in selective gestational screening with TPOAb and TgAb, based on history and fish consumption, and selective postpartum monitoring in TPOAb and/or TgAb+ve women. The 100% sensitivity, specificity and diagnostic accuracy of strategy [a] were counterbalanced by the highest costs (Euro 32,960 or 523 per each PPT caught). The corresponding numbers for strategy [k] were 78%, 95%, 93%, and Euro 8,920 or 182/PPT caught. These savings stem from gestational screening being done in 186 women, and postpartum monitoring done in 65/186 women. One gestational screning-free strategy was the cheapest (Euro 2,080 or 83/PPT caught), because based on postpartum monitoring of only 26 women, but had the lowest sensitivity (40%). Identification of pregnant women having different risks for PPT is feasible, with the costless evaluation of history and seafood consumption driving gestational screening of thyroid antibody status and postpartum monitoring of thyroid function.